The Role of Local Mass Media in the Publicity of Public Policy in Yogyakarta - PERMATASARI, ANE (Universitas Muhammadiyah Yogyakarta, 2013)
The objective of this research is to study the role of local mass media in the publicity process of a publicpolicy. Media is considered to hold the power to construct an agenda concerning on particular issues orincidents so that they gain public’s attention. Media highlights the issues by providing space and time sothat public is continuously exposed and eventually aware of the particular issue, and people deem it asimportant and build their belief on it. The method employed in this research is phenomenologicalqualitative. The apparoach is characterized by its actual setting, in that the researcher is the keyinstrument, and the data is descriptive in nature. This means that this reasearch aims to obtain datadescription that describe the composition and characteristics of the unit being studied. The result showsthat Public Policy on gender mainstreaming as stated in Presidential Instruction No. 9/2000 on GenderMainstreaming - requiring at least 5 media taken as sample of this research – is considered notnewsworthy so that the frequency of the issue reporting in mass media is very rare, or even, never exists.